Who wants a political classroom? Attitudes toward teaching controversial political issues in school - Gindi, Shahar; Gilat, Yitzhak; Sagee, Rachel (JSSE - Journal of Social Science Education, 2021)
The study examined teachers’, parents’ and students’ attitudes toward controversial political issues (CPI). A Random stratified sample of 501 adults and 201 high school students completed questionnaires. Respondents had little confidence in teachers’ ability to conduct CPI discussions in classrooms. Students reported low incidents of CPI discussions in classrooms. Support for CPI discussions differed according to specific topics. Purpose: Many argue for the benefits of controversial political issues (CPI) discussions but little is known about teachers’, parents’, and students’ attitudes toward CPI. The present study explored these attitudes, as well as attitudes towards specific controversial topics, and how they relate to socio-demographic variables. Design/methodology/approach: Quantitative cross-sectional methodology was employed using questionnaires to collect data. Random stratified sampling was used to obtain a representative sample of 501 Jewish Israeli adults, including 70 teachers, and 201 Jewish Israeli 10th-12th grade students. Findings: Respondents, including the teachers themselves, had little confidence in teachers’ ability to conduct CPI discussions in classrooms. Students reported low incidents of CPI discussions in classrooms, and that they are mostly held by homeroom and civics teachers. Students supported CPI discussions more than adults (including teachers) and wanted teachers to disclose their opinions much more than adults did. Support for CPI discussions differed according to specific topics. Linear regression revealed that the less religious individuals are, the more left-wing, older and more educated, the more they will support CPI teaching.